P-258 Impact of Direct Unequal Cleavage (DUC) on embryo development, blastocyst formation and ploidy - artificial intelligence (AI) analysis. (30th June 2022) - Florek, A; Odia, R; Theodorou, S; Duran, M; Saab, W; Seshadri, V; Serhal, P; Hickman, C; Brualla Mora, A; Derrick, R; Gaunt, M
Abstract: Study question: Do DUCs significantly impact embryo development? In particular, morphokinetics, grading, and Pre-implantation Genetic Testing for Aneuploidy (PGT-A) outcome? Is this analysis corroborated by artificial intelligence? Summary answer: DUC embryos develop slower, have lower rates of blastulation and lower CHLOE (Fairtility) scores for blastulation and implantation. However, occasionally euploid blastocysts form from DUCs. What is known already: Time-lapse technology enables the identification of DUCs during embryo development. Previous research associates DUCs with poorer blastulation, implantation, and ploidy outcomes. However, DUCs are not routinely annotated in all clinics. Some algorithms, deselect embryos with short second cell cycles; hence, DUCs are rarely transferred. Whether DUC embryos should be automatically discarded or deprioritised is an ongoing debate which leads to inconsistency in clinical practices across fertility centres. AI image processing algorithms may assist embryologists in the identification of DUCs. Study design, size, duration: A retrospective single-centre study of normally-fertilised embryos cultured in time-lapse incubators throughout 2019–2021. We reviewed 9284 time-lapse videos using an AI image processing tool (CHLOE, Fairtility), and assessed DUC embryo outcomes (ploidy, blastulation, and blastocyst quality). Additionally, we analysed pronuclei data searching for possible causes of DUCs. Participants/materials, setting, methods: CHLOE (Fairtility) software analysed time-lapse videos identifying pronuclei, DUCs, and blastulation; recording all morphokinetic time points (tPNa, tPNf, t2, t3, t4, t5, t6, t7, t8, t9, tM, tSB, tB, tEB), morphological grades for the inner cell mass (ICM) and trophectoderm, blastocyst size at 116hpi; and assessing the likelihood of blastulation (at 30hpi) and implantation. We evaluated the statistical significance for all variables using t-tests (continuous variables) and chi-squared tests (categorical variables). We quantified the two pronuclei (2PN) detection efficacy using four metrics: accuracy, sensitivity, specificity, and informedness. Main results and the role of chance: Of all the embryos analysed (n = 9284), 35% showed DUCs (n = 3269). Blastulation was significantly higher in non-DUC versus DUC embryos (76% and 49%, p < 0.0001). Of the embryos that blastulated, ICM quality (A, B, C, D: 24%, 13%, 19%, 21% and 3%, 4%, 16%, 47%, p < 0.001) and trophectoderm quality (20%, 21%, 15%, 23% and 2%, 7%, 14%, 52%, p < 0.0001) were significantly higher in non-DUC than in DUC embryos. As defined, DUC embryos were significantly quicker at reaching t3 than non-DUC [Mean(SD): 34(15) and 39(10), p < 0.0001], with the minimum times being 4hpi and 13hpi respectively. Interestingly, there was no significant difference in achieving t5 [52(21) and 51(12), NS]. For all other morphokinetic milestones, DUC embryos were 6 hours slower than non-DUC embryos. DUC embryos had an euploidy rate of 27.2% (12/44). Only one DUC embryo was transferred in a double embryo transfer cycle leading to a negative outcome. Implantation score [0.14(0.24) and 0.46(0.36), p < 0.0001] and blastulation score [0.4(0.46) and 0.75(0.4), p < 0.0001] were lower for DUC embryos than for non-DUC embryos. CHLOE automatic PN assessment agreed with human annotation in 92% of cases (TP = 388, TN=5, FP=29, FN=7). CHLOE Blastocyst prediction at 30hpi had an AUC of 0.89. The embryologist agreed on 97% of all 483 embryos that CHLOE classified as DUC. Discrepancies arose from CHLOE misclassifying fragments as blastomeres. Further studies warranted. Limitations, reasons for caution: Differentiating between fragments and blastomeres within the 5 hours from the first division proves challenging for embryologists and, especially, AI algorithms. Hence, some embryos' DUC status may be misclassified. Additionally, our sample sizes are limited and larger sizes are needed to corroborate our findings, especially those pertaining to ploidy status. Wider implications of the findings: DUC embryos are associated with poorer outcomes and DUC status should be integrated into embryo classification frameworks. Nevertheless, some DUC embryos prove to be euploid. Hence, DUC embryos should not excluded from culture at cleavage stage and instead be allowed to reach blastocyst stage before assessing their suitability for transfer/vitrification/PGT-A. Trial registration number: IRB-001C01-01-22